Pengaruh Penggunaan Media Smart Box terhadap Hasil Belajar Bahasa Inggris Materi “Telling Time” Siswa Kelas IV SDN Bulak Banteng 1/263 Surabaya - Fadila, Marshanda Nur; Rozie, Fachrur (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the impact of implementing Smart Box as learning media in English lessons, specifically on the topic of Telling Time. The research design used is a One Group Pretest-Posttest, utilizing a quantitative research approach. Data analysis used the normality test, N Gain test and t test (t test) with the help of SPSS 23. The research results showed that there was an increase in student learning outcomes using Smart Box media in learning English. This is proven by the increase in the average pretest and posttest results. In the pretest, students got an average score of 51.20 and in the posttest they got a score of 82.58. The increase can also be seen from the results of hypothesis testing, namely obtained t = 14.515 and t table 2.048 showing a significant influence so that ha is accepted